Which shows the following expression after the negative exponents have been eliminated? m 7 n...

Reece Black

Reece Black

Answered

2022-11-26

Which shows the following expression after the negative exponents have been eliminated? m 7 n 3 m n 1 ,   m ! = 0 ,   n ! = 0

Answer & Explanation

beechenUSR

beechenUSR

Expert

2022-11-27Added 8 answers

Consider the given expression.
m 7 n 3 m n 1
It is also given that m and n are non-zero values.
m 7 n 3 m n 1 = ( m 7 m ) ( n 3 n 1 ) m 7 n 3 m n 1 = ( m 7 1 ) ( n 3 ( 1 ) ) m 7 n 3 m n 1 = ( m 6 ) ( n 4 ) m 7 n 3 m n 1 = m 6 n 4

Do you have a similar question?

Recalculate according to your conditions!

Ask your question.
Get your answer.

Let our experts help you. Answer in as fast as 15 minutes.

Didn't find what you were looking for?